Hierarchically Ordered Perovskites with High Photo‐Electronic and Environmental Stability via Nanoimprinting Guided Block Copolymer Self‐Assembly. Issue 16 (31st March 2022) - Han, Hyowon; Oh, Jin Woo; Park, Jumi; Lee, Hyeokjung; Park, Chanho; Lee, Seung Won; Lee, Kyuho; Jeon, Seungbae; Kim, Sohee; Park, Youjin; Jeong, Beomjin; Ryu, Du Yeol; et al.
Abstract: The development of a sub‐50 nm nanopattern of a thin perovskite film is of significant interest with its excellent photo‐electronic properties and environmental stability. By employing nanoimprinting of a moldable perovskite precursor, self‐assembled with a block copolymer, a thin perovskite nanopattern with excellent photo‐electronic stability is developed over a large area. Approximately 40 nm nanodomains consisting of perovskite crystals, which are 10 nm in diameter, are templated in the block copolymer, and the registry of the perovskite nanodomains is further guided by the topological pattern with a periodicity of a few hundred nanometers. This method can produce hierarchically controlled nanostructures of the perovskites from molecular crystals to self‐assembled domains with tens of nanometer scale and patterned structures of a few hundred nanometers. With an ultrathin top skin layer on a patterned perovskite/block copolymer film developed during the nanoimprinting, the hierarchically ordered perovskite is environmentally stable in ambient conditions over 100 days with its photoluminescence quantum yield of ≈28%. Furthermore, the enhanced photoconduction of the perovskite nanocrystals hierarchically structured in the nanopatterns allows for developing the arrays of photodetectors with long‐term environmental stability over 90 days. Abstract : A simple but robust route employing nanoimprinting of perovskite films with self‐assembly of block copolymer successfully fabricates hierarchically ordered perovskites consisting of periodic lines and self‐assembled nanostructures. Hierarchically ordered perovskites with top skin layer effectively protecting patterns show not only significantly enhanced photoluminescence but also environmental stability, making them suitable as highly stable photoactive channels of photodetectors.